Land use pattern and sustainability of food crop production in the fadama of Southern Guinea Savanna of Nigeria - A. F. Lawal; O. A. Omotesho; M. O. Adewumi (African Journal of Environmental Economics and Management, 2013)
An assessment of the sustainability of food crop production in the fadamas of Southern Guinea Savanna of Niger State, Nigeria was carried out within the framework of small-scale farming households utilizing fadama for the cultivation of food crops. The study determined profitability of food crop production in the fadama and identified the pattern of land use and management and its effects on sustainability of fadama. A two- stage simple random sampling technique was used to obtain 149 food crop farming households interviewed for the study. The data were analyzed by using descriptive statistics such as frequency distribution, mean, standard deviation, in addition estimates of crop diversification index (CDI), nutrient intake index (NII), Ruthberg index, farm budgeting model was made. A typical household hectared seventeen persons and planted an average of 3.44 ha scattered in three plots. The major enterprises were sole crop rice and maize – based mixtures in about 0.70 and 2.59 ha respectively. Estimated mean CDI was 0.651 implying stability of income and sustainability of mixed crop enterprises while mean NII was 1.89 showing that combined crops hectareve low tendency to deplete soil nutrient. The Ruthberg index value of 0.393 implied that a six years fallow period alone may not be adequate to restore natural fertility. The farm budget analysis showed thectaret the sampled fadama food crop farming household hectared positive net return for all enterprises. Maize/cowpea enterprise hectared the highest gross margin of N25, 663/ ha while leafy vegetables (for example spinach) hectared the highest return on investment (2.39). The average return on investment for all the farms studied was 1.89. Mixed cropping the dominant cropping system generally adopted by the fadama farming households gave higher gross margin per hectare. The study concluded that production of food crop in the fadama of the Guinea Savanna of Niger State, Nigeria is sustainable. Mixed cropping, consolidation of household resources, increased use of animal traction and organic fertilizer as well as integrated pest management is recommended. In order for the foregoing to be effective, they must be accompanied by improved extension service delivery, aggressive adult education programme, regulated use of agro-chemical, improved access to credit and availability of subsidized inputs.